Chile : Review Under the Flexible Credit Line Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Chile. (IMF Staff Country Reports; Country Report ;, 2021)
The pandemic hit the Chilean economy while it was recovering from the 2019 social unrest. The authorities' swift and strong economic policy efforts and Chile's very strong institutional frameworks helped buffer the economic and social consequences. The ongoing economic recovery continues to be supported by ample policy stimulus, a rapid vaccination process, well-anchored inflation expectations, a resilient export base, and continued market confidence.